PENGARUH STORE IMAGE TERHADAP STORE LOYALTY DAN PERCEIVED QUALITY SEBAGAI MEDIASI DI WARUNG KOPI SOLONG ULEE KARENG KOTA BANDA ACEH - Afrizal Maulana; Abdul Rahman Lubis (Jurnal Manajemen Inovasi, 2019)
AbstractThis study aims to measure the effect of store image on store loyalty and perceived quality as a mediation at Solong Ulee Kareng coffee shop Banda Aceh city. The sample used in this study is Solong Ulee Kareng coffee shop customer in Banda Aceh is totaling 120 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Purposive Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that store imagepositively influence store loyalty, store imagepositively influence perceived quality, perceived qualitypositively influence store loyaltyand perceived qualitymediate the relationship between store image and store loyalty. KeywordsStore Image,Perceived Quality, Store Loyalty,Hierarchical Linear